1998
DOI: 10.1124/mol.54.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Rat α3/β4 Subtype of Neuronal Nicotinic Acetylcholine Receptor Stably Expressed in a Transfected Cell Line: Pharmacology of Ligand Binding and Function

Abstract: We stably transfected human kidney embryonic 293 cells with the rat neuronal nicotinic acetylcholine receptor (nAChR) alpha3 and beta4 subunit genes. This new cell line, KXalpha3 beta4R2, expresses a high level of the alpha3/beta4 receptor subtype, which binds (+/-)- [3H]epibatidine with a Kd value of 304+/-16 pM and a Bmax value of 8942 +/- 115 fmol/mg protein. Comparison of nicotinic drugs in competing for alpha3/beta4 receptor binding sites in this cell line and the binding sites in rat forebrain (predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
207
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(228 citation statements)
references
References 31 publications
20
207
1
Order By: Relevance
“…2). Likewise, it is probable that desensitization of the lower affinity putative ␣3␤4*-nAChRs, as observed in various cells representative of both the autonomic nervous system and CNS (Higgins and Berg, 1988;Oortigiesen and Vijverberg, 1989;Mathie et al, 1990;Khiroug et al, 1997Khiroug et al, , 1998Boyd, 1987;Ifune and Steinbach, 1993;Lester and Dani, 1995), in addition to systems designed to specifically express ␣3␤4 receptors (Cachelin and Jaggi, 1991;Hsu et al, 1996;Fenster et al, 1997;Wang et al, 1998;Xiao et al, 1998), can also be explained in terms of the two-state model, although due to the slower time course of desensitization for ␤4 subunit-containing receptors (see below), the biphasic nature may only be seen clearly during longer agonist applications (e.g., Lester and Dani, 1995). Concentration-dependent analyses of desensitization of presumed native ␣3␤4* nAChRs have estimated the affinity of the desensitized state for nicotine to be Ϸ20 -300 nM (Higgins and Berg, 1988;Lester and Dani, 1995).…”
Section: Heteromeric ␣␤* Receptorsmentioning
confidence: 99%
“…2). Likewise, it is probable that desensitization of the lower affinity putative ␣3␤4*-nAChRs, as observed in various cells representative of both the autonomic nervous system and CNS (Higgins and Berg, 1988;Oortigiesen and Vijverberg, 1989;Mathie et al, 1990;Khiroug et al, 1997Khiroug et al, , 1998Boyd, 1987;Ifune and Steinbach, 1993;Lester and Dani, 1995), in addition to systems designed to specifically express ␣3␤4 receptors (Cachelin and Jaggi, 1991;Hsu et al, 1996;Fenster et al, 1997;Wang et al, 1998;Xiao et al, 1998), can also be explained in terms of the two-state model, although due to the slower time course of desensitization for ␤4 subunit-containing receptors (see below), the biphasic nature may only be seen clearly during longer agonist applications (e.g., Lester and Dani, 1995). Concentration-dependent analyses of desensitization of presumed native ␣3␤4* nAChRs have estimated the affinity of the desensitized state for nicotine to be Ϸ20 -300 nM (Higgins and Berg, 1988;Lester and Dani, 1995).…”
Section: Heteromeric ␣␤* Receptorsmentioning
confidence: 99%
“…The up-regulation of receptor numbers does not appear to be under transcriptional regulation (Marks et al 1992). Rather, the increases may be related to changes in receptor turnover based on receptor desensitization, subunit composition, secondary structural changes in the receptor, or to modification of the receptor by protein kinases (Peng et al 1994;Baenziger and Chew 1997;Eilers et al 1997;Flores et al 1997;Hsu et al 1997;Xiao et al 1998;Fenster et al 1999).In spite of the high degree of nicotine self-administration in schizophrenics (Lohr and Flynn 1992;Ziedonis et al 1994;de Leon et al 1995), few studies have examined the effect of smoking or neuroleptic treatment on nicotinic receptor regulation in this disease (Dalack et al 1998). It has been suggested that nicotine self-administration in schizophrenics may control a neuronal deficit.…”
mentioning
confidence: 99%
“…The up-regulation of receptor numbers does not appear to be under transcriptional regulation (Marks et al 1992). Rather, the increases may be related to changes in receptor turnover based on receptor desensitization, subunit composition, secondary structural changes in the receptor, or to modification of the receptor by protein kinases (Peng et al 1994;Baenziger and Chew 1997;Eilers et al 1997;Flores et al 1997;Hsu et al 1997;Xiao et al 1998;Fenster et al 1999).…”
mentioning
confidence: 99%
“…A eukaryotic expression construct was made using the full-length cDNA of the rat α7 subunit gene (a generous gift from Dr James W PATRICK of Baylor College of Medicine). Transfection of HEK-293 cells, and selection and establishment of stable cell lines were carried out as described previously [27] , with minor modifications. Briefly, transfections were carried out using Lipofectamine 2000 transfection reagent (Invitrogen Corp).…”
Section: Introductionmentioning
confidence: 99%
“…Stably transfected mammalian cell lines heterologously expressing neuronal nAChR subtypes have been powerful tools to study neuronal nAChRs [11,[27][28][29][30][31][32] . Several such cell lines expressing functional α7 nAChRs were successfully established in recent years, including the rat α7 subunit gene expressed in SH-SY5Y human neuroblastoma cells, which also express endogenous nAChR α3, α5, α7, β2, and β4 subunit genes [33] ; the human α7 subunit gene expressed in HEK-293 cells [11] and in SH-EP1 clonal human epithelial cells [34,35] , both of which are devoid of endogenous nAChR subunits; and the rat α7 subunit gene expressed in GH 4 C 1 clonal rat pituitary cells, which endogenously express the rat nAChR β4 subunit gene [36,37] .…”
Section: Introductionmentioning
confidence: 99%